Photocatalytic Degradation of Monolinuron and Linuron in an Aqueous Suspension of Titanium Dioxide Under Simulated Solar Irradiation - Zouaghi, Razika; Zertal, Abdennour; David, Bernard; Guittonneau, Sylvie (Revue des sciences de l'eau / Journal of Water Science)

(untitled) (Université du Québec - INRS-Eau, Terre et Environnement (INRS-ETE), 2007)
AbstractThe photocatalytic degradation of two phenylurea herbicides, monolinuron (MLN) and linuron (LN), was investigated in an aqueous suspension of TiO2 using simulated solar irradiation. The objective of the study was to compare their photocatalytic reactivity and to assess the influence of various parameters such as initial pesticide concentration, catalyst concentration and photonic flux on the photocatalytic degradation rate of MLN and LN. A comparative study of the photocatalytic degradation kinetics of both herbicides showed that these two compounds have a comparable reactivity with TiO2/simulated sun light. Under the operating conditions of this study, the photocatalytic degradation of MLN and LN followed pseudo first-order decay kinetics. The kobs values indicated an inverse dependence on the initial herbicide concentration and were fitted to the Langmuir-Hinshelwood equation. Photocatalytic degradation rates increased with TiO2 dosage, but overdoses did not necessarily increase the photocatalytic efficiency. The degradation rate of MLN increased with radiant flux until an optimum at 580 W m‑2 was reached and then decreased. Under these conditions, an electron-hole recombination was favored. Finally, the photocatalytic degradation rate depended on pH, where an optimum was found at a pH value close to the pH of the point of zero charge (pH = 6).